2012
DOI: 10.1002/ar.22551
|View full text |Cite
|
Sign up to set email alerts
|

Reversal Effect of Melanoma Differentiation Associated Gene‐7/Interleukin‐24 on Multidrug Resistance in Human Hepatocellular Carcinoma Cells

Abstract: Multidrug resistance is the main cause for failure of chemotherapy. Melanoma differentiation associated gene-7/interleukin-24 (mda-7/IL-24) has been implicated in the inhibition of human tumor cell proliferation. However, the reversing effect of mda-7/IL-24 on multidrug resistance of human hepatocellular carcinoma (HCC) is not fully clear. In this study, we investigated the effects of overexpression of the mda-7/IL-24 gene in human HCC. We established mda-7/IL-24 overexpressing BEL-7402/5-fluorouracil (5-FU) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…MTS assay results showed that Mda-7/IL-24 significantly retarded proliferation of Raji and Daudi cells, and enhanced the sensitivity of these lymphoma cells to various chemotherapy drugs, including CDDP, epirubicin and VCR, and that IC 50 was lower in cells transfected with Mda-7/IL-24 than in non-transfected and vector-transfected cells. These results were in good agreement with the effects of Mda-7/IL-24 on these types of tumor cells (2,5,6). In addition, although the apoptosis-inducing capability of Mda-7/IL-24 has been widely documented in various solid tumors, we did not observe significant induction of apoptosis in the two lymphoma cell lines.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…MTS assay results showed that Mda-7/IL-24 significantly retarded proliferation of Raji and Daudi cells, and enhanced the sensitivity of these lymphoma cells to various chemotherapy drugs, including CDDP, epirubicin and VCR, and that IC 50 was lower in cells transfected with Mda-7/IL-24 than in non-transfected and vector-transfected cells. These results were in good agreement with the effects of Mda-7/IL-24 on these types of tumor cells (2,5,6). In addition, although the apoptosis-inducing capability of Mda-7/IL-24 has been widely documented in various solid tumors, we did not observe significant induction of apoptosis in the two lymphoma cell lines.…”
Section: Discussionsupporting
confidence: 90%
“…Studies are required to elucidate the mechanisms of drug resistance, and new treatment strategies are needed to improve cure rates and survival in patients with lymphoma. Changes in molecular regulatory networks that increase anti-apoptotic activity and reduce the apoptosis of tumor cells are the primary mechanisms associated with resistance to chemotherapy drugs (2,17). Methods of enhancing sensitivity to chemotherapy and avoiding MDR remain among the most difficult problems in tumor treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At present, chemotherapy agents-based strategies remain the first choice for treatment of T-cell lymphoma, however poor prognosis is inevitable due to the occurrence of multidrug resistance (MDR) (2). The typical MDR phenotype is characterized by the overexpression of the MDR-associated proteins in the cytomembrane that serve as efflux pumps, to exclude the intracellular antitumor agents (3,4).…”
Section: Introductionmentioning
confidence: 99%